Perioperative nursing care of a case of acute incarceration of complete rectal prolapse (1例急诊完全性直肠脱垂嵌顿患者的围手术期护理) - WANG Xueliang (王雪亮); LENG Yu (冷羽); XIE Wei (谢薇); LI Zhi (李志); ZHANG Fang (张芳); FENG Lin (冯琳); CHEN Lei (陈磊) (Association of Integrative Nursing, 2023)
The perioperative nursing experience of an emergency case of incarcerated complete rectal prolapse was summarized. The key points of nursing include protecting the wound and improving preoperative preparation actively; Rapid establishment of intraoperative venous access; Postoperative recurrence avoidance, diet nursing, disease observation, fluid management, etc. (总结1例急诊完全性直肠脱垂嵌顿患者的围手术期护理经验。护理要点包括保护创面、积极完善术前准备; 术中快速建立静脉通路; 术后避免复发、饮食护理、病情观察、液体管理等。)